1977
DOI: 10.1021/ja00467a012
|View full text |Cite
|
Sign up to set email alerts
|

Chromium(III) porphyrins. Chemical and spectroscopic properties of chloro-meso-tetraphenylporphinatochromium(III) in nonaqueous solutions

Abstract: The spectroscopic and chemical behavior of the six-coordinate adducts formed by the association of chloro-meso-tetraphenylporphinatochromium(III), Cr(TPP)(CI), and neutral oxygen, sulfur, and nitrogen donor ligands in nonaqueous solutions is described. In nonaqueous media, in the presence of a neutral ligand, Cr(TPP)(CI) forms six-coordinate adducts of the type Cr(TPP)(CI)(L) and Cr(TPP)(CI)(B), where L and B denote neutral N-donor and 0-or S-donor ligands, respectively. This behavior is confirmed by visible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
71
2

Year Published

1978
1978
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 9 publications
10
71
2
Order By: Relevance
“…MTPPCl species have favorable binding energies for pyridine coordination via reaction (I). This is known experimentally for CrTPPCl [45]. Although the energy of reaction (II) is unfavorable for Fe, the energy of reaction (I) is sufficiently large that the formation of the bis-pyridine adduct is exothermic.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 65%
“…MTPPCl species have favorable binding energies for pyridine coordination via reaction (I). This is known experimentally for CrTPPCl [45]. Although the energy of reaction (II) is unfavorable for Fe, the energy of reaction (I) is sufficiently large that the formation of the bis-pyridine adduct is exothermic.…”
Section: Density Functional Theory Calculationsmentioning
confidence: 65%
“…Except for Cr-TPPCl, all porphyrin dyes, Zn-TPPD [Tokyo Chemical Industry Co., Ltd. (TCI), Tokyo, Japan], TPFPP (TCI), TCPP (TCI), and hemin (TCI) were commercially available and used without further purification. Cr(III)-TPPCl was prepared by a refluxing method published by Adler and coworkers [31]. H 2 TPP (1.0 g, >98.0%, chlorine free, TCI) was dissolved in 300 mL of N,N-dimethylformamide (DMF).…”
Section: Methodsmentioning
confidence: 99%
“…The spectrum of a diamagnetic chromium(IV) complex contains wellresolved tetraphenylporphyrin signals in the range 7.7839.08 ppm [12]. Comparison of the corresponding electronic spectrum (maxima and log e) with published data [4,7,15,16] provides evidence for the valence state of Cr(III). Addition of a nearly equimolar amount of imidazole has no effect on the signal of the metal complex and gives rise to fairly narrow singlets with a 1 : 2 integral intensity ratio, assignable to the protons in the 2 and 4,5 positions of the heteroring [17].…”
mentioning
confidence: 88%
“…According to [9,10], in aqueous solutions Cr(III) complexes tend to lose the acido ligand localized in the fifth coordination position to give charged bisaqua complexes whose reaction with imidazole gives rise to bisimidazole derivatives. Conductometric and spectral studies [4,13] showed that in organic solvents (acetonitrile, DMSO) coordination of heterocycles involves no dissociation of acido ligand and formation of charged complexes, whereas analysis of the electronic absorption spectra of chromium(III) (acetate)tetraporphyrinate (AcO)CrTPP in toluene made Tipugina and Lomova [8] to suggest that axial coordination involves formation of ion pairs. Figure 1 illustrates the changes in the electronic absorption spectra, produced by addition of imidazole (Im) into a solution of (AcO)CrTPP in ethanol.…”
mentioning
confidence: 99%
See 1 more Smart Citation